THE INFLUENCE OF CASH TURNOVER, RECEIVABLES TURNOVER, INVENTORY TURNOVER AND WORKING CAPITAL SPREAD ON PROFITABILITY IN COAL MINING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2017-2021 PERIOD - ,; ,; ,; ,; , (LUCRUM : Jurnal Bisnis Terapan; Vol 4 No 4 (2024): LUCRUM : Jurnal Bisnis Terapan, 2025)
There are many factors that affect the high and low profitability of a company such as liquidity, company size, company age, company growth, working capital, and cash ratios. This study aims to determine the effect of cash turnover, accounts receivable turnover, inventory turnover and working capital turnover on profitability. The population of this research is the 28 best companies listed on the Indonesian stock exchange (IDX) for the 2017-2021 period. The sampling technique used is purposive sampling, so there are 22 sample companies. The data analysis technique used is multiple linear regression analysis using spss software. The results of this study indicate that working capital turnover has a significant effect on profitability while cash turnover, accounts receivable turnover and inventory turnover have no effect on profitability.